Dinamika Pendidikan Masyarakat Nelayan Di Desa Pandangan Wetan Kecamatan Kragan Kabupaten Rembang - Fatwa, Moh. Saiful (Forum Ilmu Sosial, 2016)
Public of education level affects the mindset and perceptions about the important role of education for their children. The purpose of this study was to determine the social conditions of fishermen, Fishermen's commitment to education and family know the child's behavior in theÂ  Fishermen families Desa Kragan Pandangan wetanRembang. The method used is qualitative, and data collection techniques is using interviews, observation and document study. The data analysis technique used in this study is an interactive model with step data collection , data reduction , data presentation and conclusion. The validity of the data is done by means of triangulation of methods and sources.Results showed (1) in general and most of the views of parents/fishing Pandega to education is low, (2) Fishermen Family Commitment to education children affected fishermen families where parenting in general and most of the families of fishermen inthe village of view Wetan District of Kragan is authoritarian parenting and permissive parenting, because many parents in the Desa Kragan Pandangan Wetan Rembang is overbearing in certain fields such as educatio, (3) in general, and most forms of social behavior of children, including good. Any violation by the respondent is still in reasonable category. Based on the observations by researchers in the environment where he lives, the children of fishermen Pandega majority being nice , hardworking and obedient to his parents .